Sustained Neglect in Mental Health during Nepal’s Crises - Mishra, Shiva Raj; Khanal, Pratik; Khanal, Vishnu (Health Prospect, 2018)
Conflict in Nepal seems never resolving and the current generation has grown up in the environment of armed and political conflict characterized by indiscriminate killing, violent demonstration and widespread hostility. Adding to agony, the April 2015 earthquake left two million homeless and the 2015 Indo-Nepal economic blockade has created hostility among different community ethnic groups. With such background, this commentary highlights issues related to conflict, disaster and their relation to mental health. We also identify some gaps in existing health system, medical education and current focus on preventive approach to mental health. Mental health policy was endorsed in 1996; however, the policy has never been implemented in the fullest sense. Psychiatric services are provided by tertiary hospitals with no linkage to community-level primary health care services. Medical training still lacks mental health training at basic cadres of health workers and only small number of seats is allocated for post-graduate degree. Nepal continue to experience conflicts and disasters possibly leading to an increased burden of mental health problems and its health system is further distressed by the increasing gaps in provision of mental health service. With the devastating effect of the April 2015 earthquake, there is even higher need of serious effort to treat and prevent mental health problems with evidence-though limited depicting increase in burden of mental health problems. The state should stop putting half-hearted response to mental health problems and put more effort on long-term sustainable and culturally suitable solutions. Keywords: conflict, mental health, Nepal